Allelopathy a Tool for Sustainable Weed Management - , K. H. Shirgapure; , Pritam Ghosh (Archives of Current Research International, 2020)
Phytochemicals released by plant species into the environment inhibit the emergence and growth of surrounding plants by changing their metabolic activity or impacting on their soil community mutualists referred as allelopathy. Allelochemicals are the compounds produced from the secondary metabolism of higher plants and microorganisms such as fungi, bacteria and viruses and affect on many processes in ecosystems and agro-ecosystems. In complex agro-ecosystem both crop and weed shows allelophathic effect. Allelochemicals from crop plant affect on other crop and weed while allelochemicals from weed effect on other weed and crop, beside this both weed and crop also shows autoallelopathy. Hence scientific and proper estimation of allelopathic plant, their allelochemical and susceptible weed species is necessary through advance research. This is helps to increase agricultural production, reduction in cost of pesticides, environment hazard, and way for the sustainable weed management and sustainable development of agricultural production as well as ecological systems.